Biphasic bone substitutes coated with PLGA incorporating therapeutic ions Sr2+ and Mg2+: cytotoxicity cascade and in vivo response of immune and bone regeneration - Ren, Yanru; Jung, Ole; Batinic, Milijana; Burckhardt, Kim; Görke, Oliver; Alkildani, Said; Köwitsch, Alexander; Najman, Stevo; Stojanovic, Sanja; Liu, Luo; Prade, Ina; Barbeck, Mike (Frontiers in Bioengineering and Biotechnology, 2024)
The incorporation of bioactive ions into biomaterials has gained significant attention as a strategy to enhance bone tissue regeneration on the molecular level. However, little knowledge exists about the effects of the addition of these ions on the immune response and especially on the most important cellular regulators, the macrophages. Thus, this study aimed to investigate the in vitro cytocompatibility and in vivo regulation of bone remodeling and material-related immune responses of a biphasic bone substitute (BBS) coated with metal ions (Sr 2+ /Mg 2+ ) and PLGA, using the pure BBS as control group. Initially, two cytocompatible modified material variants were identified according to the in vitro results obtained following the DIN EN ISO 10993-5 protocol. The surface structure and ion release of both materials were characterized using SEM-EDX and ICP-OES. The materials were then implanted into Wistar rats for 10, 30, and 90 days using a cranial defect model. Histopathological and histomorphometrical analyses were applied to evaluate material degradation, bone regeneration, osteoconductivity, and immune response. The findings revealed that in all study groups comparable new bone formation were found. However, during the early implantation period, the BBS_Sr 2+ group exhibited significantly faster regeneration compared to the other two groups. Additionally, all materials induced comparable tissue and immune responses involving high numbers of both pro-inflammatory macrophages and multinucleated giant cells (MNGCs). In conclusion, this study delved into the repercussions of therapeutic ion doping on bone regeneration patterns and inflammatory responses, offering insights for the advancement of a new generation of biphasic calcium phosphate materials with potential clinical applicability.